PEMBUKTIAN TINDAK PIDANA PENADAHAN KENDARAAN BERMOTOR OLEH KEPOLISIAN RESOR KOTA PEKANBARU PADA TINGKAT PENYIDIKAN - Khoirunnisak '; Erdianto '; Ledy Diana (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2016)
Crime fencing is a criminal offense possessions where rampant today in Pekanbaru. Though this criminal act has been formulated in the Penal Code Article 480 and have sanctions. For it is necessary to review how evidence fencing motor vehicle criminal offenses by police investigators from the resort town of Pekanbaru.From this research, there are three main things that author can conclude .First, On the implementation of proving the crime of motor vehicles in the investigations level in POLRESTA Pekanbaru is with the collection of evidence that a criminal act becomes light for use as a material proof so it can be directly transferred to kejaksaan. Second , barriers which faced by POLRESTA Pekanbaru in proving the crime of motor vehicle fencing which comes from internal and external factors. Third, Pekanbaru POLRESTA efforts in overcoming the obstacles encountered in proving the crime of motor vehicle fencing in cooperation with various parties, sanctions to perpetrators of criminal acts motor vehicle fencing. Author, First Socialization to the community, Second, improve cooperative relationships with related parties..Keywords: Verificatiom– Investigation – Fencing